Hoffnung's The Maestro - Hoffnung, Gerard 1925-1959 (London The Hoffnung Partnership, 2000)
There can be few conductors who have not laughed out loud at these cartoons and found a modicum of truth in them. In these 50 drawings, commencing with alerto, embracing con anima, con delicatezza, and molto pomposo, then on to appassionato until the final triumph (and relief) of bravo bravissimo, here is an affectionate and genial glimpse into the mystique surrounding the Maestro together with a loving appraisal of his antics.